Infecção bacteriana em pacientes portadores de Leishmaniase visceral Bacterial infection in patients with visceral leishmaniasis - Jaqueline Guerreiro; Samia Ribeiro; Edgar M. Carvalho; Roberto Badaró; Heonir Rocha (Memorias do Instituto Oswaldo Cruz, 1985)
Uma análise retrospectiva de 63 casos de Leishmaniose visceral (L.V.) revelou a presença, em 33 deles, de infecção bacteriana associada. Infecções do trato respiratório foram observadas em 13 (39,3%) pacientes, comprometimento de pele em 4 (12%), do trato urinário em 4 (12%), do ouvido em 3 (9%), e de orofaringe em 2 (6%). Sete (21%) pacientes apresentaram infecção concomitante em múltiplos sítios. Documentação bacteriológica através de isolamneto do agente etiológico foi obtida em 10, não havendo predominância estatisticamente significante de bactérias Gram positivas ou negativas. Houve 9 casos de óbito nestes 63 pacientes, sendo que em 8 deles a infecção bacteriana fazia parte do quadro clínico final. A análise das taxas de globulinas séricas revelou que infecção esteve presente de modo significativo (p < 0.05) em 15/20 (75%) dos pacientes com níveis de globulina sérica [menor ou igual a] 4,0g%. Não houve diferença significativa (p > 0.05) com relação ao número de neutrófilos entre os grupos com e sem infecção bacteriana. Concluiu-se, portanto, que infecção bacteriana é um achado freqüente em pacientes com L.V. e se constitui num sinal de mau prognóstico da doença. In an analysis of 63 hospitalized cases with visceral leishmaniasis, the clinical or post-mortem diagnosis of bacterial infection was performed in 33; 13 (39.3%) patients had respiratory infection, 4 (12.1%) had skin infection, 4 had urinary tract infection, 3 (9.0%) showed ear infection and 2 (6.6%) had infection of the oral cavity. It is worth mentioning that in 7 (21%) cases there was infection in multiple sites. Gram positive and/or Gram negative organisms were isolated from 10 patients. In only two (autopsied) cases, infection with less common organisms was recorded, one with disseminated candidiasis and another with disseminated tuberculosis. Death occurred in 9 of the 63 cases, and in 8 of these, concomitant bacterial infection of importance was documented. Patients who had serum globulins lower than 4 g% had significantly more infection (p less than 0.05) than patients with globulin levels higher than 4 g%; there was no significant difference when the number of leucocytes and neutrophils in patients with associated infection was compared with those in patients without bacterial infection. The present study demonstrates that bacterial infection frequently occurs in patients with visceral leishmaniasis, and indicates an unfavourable prognosis. Even though the mechanism of increased susceptibility to infection in this condition was unclear, the widespread range of infections and of infective agents, suggests a multifactorial process.